Toxic effects of alcohol intake on prostate of rats - Novelli, Ethel L.B. [UNESP]; Rodrigues, Ney L. [UNESP]; Santos, Célio X.C. [UNESP]; Martinez, Francisco E. [UNESP]; Novelli, José Luiz V.B. [UNESP] (My University, 1997)
BACKGROUND. The present report was carried out to determine whether alcohol intake could induce prostate lesions. METHODS. We tested male rats for 300 days. Animals were divided into three groups: controls received only tap water as liquid diet; the chronic alcohol intake group received only ethanol solution in semivoluntary research; and the withdrawal group received the same treatment as chronic alcohol intake until 240 days, after which they reverted to drinking water. RESULTS. Chronic alcohol intake increased lipoperoxide concentrations and acid phosphatase activities. Cu-Zn superoxide dismutase (SOD) was decreased at 60 days, but approached controls values at 300 days following treatment. The serum increased alkaline phosphatase, and alanine transaminase activities reflected the chronic toxic effect of ethanol. CONCLUSIONS. Since SOD activity was unable to scavenge superoxide radical and lipoperoxide formation, we can conclude that superoxide is an important intermediate in prostate damage of chronic alcohol intake.
Keywords: chronic alcohol intake; prostate; rats; superoxide radical